2022
DOI: 10.3324/haematol.2022.281482
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes control hematopoiesis and inflammation through CD40 signaling

Abstract: The co-stimulatory CD40-CD40L dyad plays an important role in chronic inflammatory diseases associated with ageing. Although CD40 is mainly expressed by immune cells, CD40 is also present on adipocytes. We aimed to delineate the role of adipocyte-CD40 in the aging haematopoietic system and evaluated the effects of adipocyte CD40 deficiency on cardiometabolic diseases. Adult adipocyte CD40-deficient mice (AdiCD40KO) mice had a decrease in bone marrow (BM) haematopoietic stem cells (Lin-Sca+cKit+, LSK) and commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the present manuscript, Reiche and colleagues demonstrated the impact of CD40 deletion in mature adipocytes on inflammation and metabolic diseases 6 . The authors generated mice selectively lacking CD40 expression on mature adipocytes (AdipoQ cre x CD40 fl/fl mice) and observed decreased bone marrow hematopoietic stem cell numbers in adult and aged mice.…”
Section: Title: Adipocytes In Their (Cd)40smentioning
confidence: 59%
See 1 more Smart Citation
“…In the present manuscript, Reiche and colleagues demonstrated the impact of CD40 deletion in mature adipocytes on inflammation and metabolic diseases 6 . The authors generated mice selectively lacking CD40 expression on mature adipocytes (AdipoQ cre x CD40 fl/fl mice) and observed decreased bone marrow hematopoietic stem cell numbers in adult and aged mice.…”
Section: Title: Adipocytes In Their (Cd)40smentioning
confidence: 59%
“…In an article published in this issue of Haematologica , Reiche and colleagues describe the impact of CD40 deletion in mature adipocytes on inflammation and metabolic diseases. 6 The authors generated mice selectively lacking CD40 expression on mature adipocytes (AdipoQ cre x CD40 fl/fl mice) and observed decreased bone marrow hematopoietic stem cell numbers in adult and aged mice. Moreover, B-cell and T-cell homeostasis was altered, with decreased numbers of B cells and T cells displaying an activated pro-inflammatory phenotype.…”
mentioning
confidence: 99%
“…Signaling and transcription factors (TRAM, MAPK, STAT5, NF-κB) Secreting cytokines (IL-12, MMPs, MIP-1, MCP-1, IL-8, TNF-α, IFN-γ) [44,60] Adipocytes, endothelial cells Promotion and formation of a stable plaque phenotype Leukocyte adhesion, inflammatory cell migration [51,52] Dendritic cells Attenuated atherosclerosis Lipid uptaking [7,56] Antigen-presenting cells CD40-TRAF2/3/5 interaction Inhibiting interaction between CD40 and TRAF6 [61,62] Endothelial cells Determining the atherosclerotic susceptibility sites Cytokines (ICAM-1, MCP-1, IL-6, IL-8, MMPs) the near future, there will be alternative approaches that are based on CD40-CD40L. As a result, the prospects for cellor signal-specific treatment of the CD40-CD40L interaction in atherosclerosis are promising and will require long-term investigation.…”
Section: Cd40 Monocytes/macrophages Regulation Of Cd40l Overexpressio...mentioning
confidence: 99%
“…In addition, CD40 deficiency has been shown to reduce the burden of atherosclerosis. [ 51 , 52 ] These findings suggest that decades of research on the CD40-CD40L interaction and atherosclerosis have identified a promising immune-therapy target for this disease with high probability.…”
Section: Cd40-cd40l and Atherosclerosismentioning
confidence: 99%
“…Other recent studies suggested that adipose tissue is a complex organ with functions well beyond the mere energy storage: of note, adipocytes are able to release a plethora of adipokines and cytokines theoretically involved in CKD-associated inflammation [ 47 ]. In this inflammatory and uremic milieu, adipocyte CD40 expression plays an important role in the preservation of immune cell homeostasis in the bone marrow during aging and inflammatory processes: in particular, CD40-deficient mice showed a decrease in hematopoietic stem cells (Lin-Sca + cKit +) and lymphoid progenitors in the bone marrow associated with increased adiposity and T cell activation, a phenotype more pronounced with age [ 48 ]. Moreover, sCD40L induces a proinflammatory phenotype and cellular differentiation in adipose tissue [ 49 ].…”
Section: Role Of the Cd40-cd40l Pathway In Tissue Agingmentioning
confidence: 99%